TOXICITY OF FOUR FUNGICIDES TO THE GROWTH AND PROTEIN AMOUNT OF CHLORELLA VULGARIS - Bedil, Burcin; Cetin, A. Kadri (Parlar Scientific Publications (P S P), 2017)
The sensitivity of different organisms to various chemicals differ from each other. In this study, the changes in the growth rate and protein amounts of the green algae Chlorella vulgaris against four different fungicides were examined. The fluid cultures that C.vulgaris is located in were subject to different fungicide concentrations. The number of cells and protein amount of C.vulgaris were examined in four day periods. It was observed that the growth rate and protein amount of C. vulgaris differed depending on the fungicide concentration and exposure time. Our results showed that the effects of the fungicides on the growth rate and protein amount of C. vulgaris were different.
Keywords: Chlorella vulgaris; fungicides; acute toxicity tests